Experimental Study on Solar Air Heating - Chaichan, Miqdam T; Ali, Ali J.; Abass, Khaleel I. (Al-Khwarizmi Engineering Journal, 2018)
Abstract  A new type of solar air heater was designed, fabricated, and tested in Baghdad, Iraq winter conditions. The heater consists of two main parts. The horizontal section was filled with the black colored iron chip while the vertical part has five pipes filled with Iraqi paraffin wax. A fan was fixed at the exit of the air. Two cases were studied: when the air moved by natural convection and when forced convection moved it. The studied air heater has proven its effectiveness as it heated the air passing through it to high temperatures. The results manifest that using little air movement makes the temperatures, stored energies, and efficiencies of the two studied cases converge. The suitable solar intensity of Baghdad city makes the use of solar air heater suitable to reduce the electricity and fossil fuels consumption.